NEEDS ANALYSIS OF INTERACTIVE VIDEO MEDIA BASED ON PROBLEM-BASED LEARNING IN MATHEMATICS CONTENT IN GRADE 4 - Laili, Tika Rohmatul; Dewi, Radeni Sukma Indra; Kusumaningrum, Shirly Rizki; Zainuddin (ELSE (Elementary School Education Journal) : Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2024)
This study aims to analyze the needs of interactive video media based on problem-based learning in Mathematics content in grade 4 of Roudlatul Jannah Islamic Elementary School. This research method is descriptive qualitative through observation techniques and interviews with 2 4th grade homeroom teachers. The results showed that teachers need interactive video media that can improve students' critical thinking skills. This is due to the lack of technology-based learning resources in the school environment. It is expected that interactive video media can be an interesting and effective teaching alternative to improve critical thinking skills in math lessons. Therefore, the development of interactive video learning media needs to be considered in preparing mathematics lesson plans in grade 4 of Roudlatul Jannah Islamic Elementary School.